Performance evaluation of symmetric cryptography algorithm for database system / Mariam Azwa Yazid - Yazid, Mariam Azwa (2015)
Cryptography has been proven to be the best method to secure a database. However there are many types of cryptography algorithm that has been established in the market. To choose the best cryptography methods requires a research to suit it with the system requirement. Normally, the performance of the encryption and decryption process is the major consideration. This research evaluates the performance of three different symmetric cryptography algorithms. A series of testing cycles has been carrier out to identify the fastest algorithm. There are three types of measurement parameters that have been used for the testing. A Database System Engine has been developed to measure the performance of the algorithm. The result of the experiment shows that the AES is the fastest algorithm compared to TripleDES and RC4. This result might give a clear idea to any organisation that would like to adopt any cryptography technique as their database security approach